Conversion Characteristics of Chemical Constituents in Liriodendron tulipifera and Their Influences on Biomass Recalcitrance during Acid-Catalyzed Organosolv Pretreatment - GWAK, Ki-Seob; SHIN, JunHo; YOON, Chae-Hwi; CHOI, In-Gyu (Journal of the Korean Wood Science and Technology, 2024)
The conversion characteristics of the major components of Liriodendron tulipifera were investigated during acid-catalyzed organosolv pretreatment. Glucan in L. tulipifera was slowly hydrolyzed, whereas xylan was rapidly hydrolyzed. Simultaneous hydrolysis and degradation of xylan and lignin occurred; however, after complete hydrolysis of xylan at higher temperatures, lignin remained and was not completely degraded or solubilized. These conversion characteristics influence the structural properties of glucan in L. tulipifera. Critical hydrolysis of the crystalline regions in glucan occurred along with rapid hydrolysis of the amorphous regions in xylan and lignin. Breakdown of internal lignin and xylan bonds, along with solubilization of lignin, causes destruction of the lignin-carbohydrate complex. Over a temperature of 160℃, the lignin that remained was coalesced, migrated, and re-deposited on the surface of pretreated solid residue, resulting in a drastic increase in the number and content of lignin droplets. From the results, the characteristic conversions of each constituent and the changes in the structural properties in L. tulipifera effectively improved enzymatic hydrolysis in the range of 140℃–150℃. Therefore, it can be concluded that significant changes in the biomass recalcitrance of L. tulipifera occurred during organosolv pretreatment. KCI Citation Count: 1